1999
DOI: 10.3109/02841859909175596
|View full text |Cite
|
Sign up to set email alerts
|

MR Assessment of Movement and Morphologic Change in the Menisci during Knee Flexion

Abstract: Knee flexion normally leads to posterior movement and shortening of the a.p. diameter of the menisci, which may be related to the positioning and curvature of femoral condyles at the femorotibial contact point at knee flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 20 publications
4
49
2
Order By: Relevance
“…11,12,[21][22][23] This corresponds with the movement of the contact centroid during flexion. The amount of movement of the meniscus and the contact centroid was similar, indicating that our results have likely captured the effects of posterior roll of the femur on the tibial plateau during flexion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12,[21][22][23] This corresponds with the movement of the contact centroid during flexion. The amount of movement of the meniscus and the contact centroid was similar, indicating that our results have likely captured the effects of posterior roll of the femur on the tibial plateau during flexion.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,[21][22][23] Von Eisenhart-Rothe et al found that meniscal movement in ACL-deficient knees is similar to that in normal knees even though bone kinematics are different. 12 We only found a difference in meniscal translation between injured and uninjured knees at one point (#6), even though the contact centroid translation was significantly different in ACLdeficient knees.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were performed with open MRI systems (0,5 T or less), and to the best of our knowledge, there isn't any study done with closed system MRI (1.5 T or more) while the knee is in flexion position. Besides, kinematic knee MRI studies are mostly done to evaluate patellofemoral joint discordance or to differentiate partial anterior cruciate ligament (ACL) rupture from total rupture, and rarely tried in meniscal lesions (7)(8)(9)(10)(11)(12)(13)(14)(15). The first kinematic MRI study to evaluate meniscal lesions and cruciate ligament lesions was done by Niitsu et al (10).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the examinations are performed with closed MRI system which has high magnetic field power (1.5 T) and high contrast resolution with an only one additional KFA sequence in order not to cause patient discomfort or too increased ex- amination time. In most of the kinematic MRI studies (7,8,(10)(11)(12)(13)(14)(15), a flexion angle of 40-50˚ could be maintained, while in a study (9) a flexion angle reaching up to 90˚ was achieved. In our study, we could maintain a flexion angle between 30-50˚ (mean: 40˚), and this was the main limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation